Sustainability of bioplastics: opportunities and challenges - Thakur, Sourbh; Chaudhary, Jyoti; Sharma, Bhawna; Verma, Ankit; Tamulevicius, Sigitas; Thakur, Vijay Kumar (Elsevier, 2018)
Recycling is groundwork of the worldwide efforts to diminish the amount of plastics in waste. Mostly around 7.8–8.2 million tons of poorly-used plastics enter the oceans every year. Non-biodegradable plastics settlements in landfills are uncertain, which hinders the production of land resources. Non-biodegradable plastic solid wastes, carbon dioxide, greenhouse gases, various air pollutants, cancerous polycyclic aromatic hydrocarbons and dioxins, released to the environment cause severe damage and harmfulness to the inhabitants. Due to the bio-degradability and renewability of biopolymers, petroleum-based plastics can be replaced with bio-based polymers in order to minimize the environmental risks. In this review article, bio-degradability of polymers has been discussed. The mechanisms of bio-recycling have been particularly emphasized in the present article.